Match and training injury epidemiology in elite UK netball: a prospective cohort study over one season - Sara Horne; Aliah F Shaheen; Bill Baltzopoulos; Laura Hills (BMJ Open Sport & Exercise Medicine)
Objective To describe the incidence and characteristics of match and training injuries in the UK Vitality Netball Superleague (VNSL).Methods Ninety players were observed over one 14-month VNSL season (2021), including pre-, in- and post-season periods. Team physiotherapists recorded injuries using an online surveillance system, classifying them by location, type, mode, mechanism and impact, including severity (time-loss days, TL) and medical attention days (MA). Injury incidence (I) and TL/MA injury burden were calculated per 1000 player hours. χ2 analysis compared match and training differences.Results Thirty-nine players sustained 70 injuries (n=35 match, 35 training). Match incidence exceeded training (I=41.12 vs 1.10 injuries). Acute injuries were higher in matches (27 vs 17), while overuse injuries were higher in training (18 vs 3; p=0.001). Contact injuries were higher in matches (21 vs 7), and non-contact injuries were higher in training (10 vs 6; p=0.028). Acute ankle ligament injuries in matches caused substantial TL burden (411.7 days lost), while overuse lower leg injuries in training led to high MA burden (13.8). Anterior cruciate ligament (ACL) injuries were infrequent but burdensome (TL 496). The centre position sustained the most injuries (41%).Conclusion This study underpinned implementing the first injury surveillance system in the elite UK netball competition, revealing match injury rates ~40 times higher than in training, with distinct injury characteristics. Findings suggest that prevention should target acute lower limb injuries and overuse conditions. Further research should assess the impact of playing with overuse injuries.